Penerapan Metode Pembelajaran Natur Learning Terhadap Peningkatan Keterampilan Menulis Puisi Siswa Kelas VIII SMP Negeri 1 Sulabesi Tengah - Boriri, Agus; Samad, Sartika; Atib, Masria; Umamit, Inda Tarah (Peneliti.net, 2025)
This study aims to (1) determine students' ability in writing poetry using the nature learning method in class VIII students of SMP Negeri 1 Sulabesi Tengah (2) describe the nature learning method can improve the poetry writing skills of class VIII students of SMP Negeri 1 Sulabesi Tengah. The type of research used in Kurt Lewin's classroom action research (PTK). The results of this study prove that the application of the nature learning method is proven to be effective in improving students' poetry writing skills. This is indicated by an increase in the average class value from 57.00 in the pre-cycle, to 75.75 in cycle I, and increasing again to 83.00 in cycle II, student learning completeness experienced a significant increase, namely from 20.59% in the pre-cycle, to 55.88% in cycle I, and reaching 94.12% in cycle II. Thus, the indicator of research success (> 85% of students achieving KKM) was achieved in cycle II.